PFKFB3 deprivation attenuates the cisplatin resistance via blocking its autophagic elimination in colorectal cancer cells - Li, Qianqian; Ma, Jianxing; Zhang, Yaqin; Sun, Fengyao; Li, Wen; Shen, Wenzhi; Ai, Zhiying; Li, Changli; Wang, Shanshan; Wei, Xiaonan; Yan, Siyuan (Frontiers in Pharmacology, 2024)
6-Phosphofructo-2-kinase/fructose-2,6-bisphosphatase isoform 3 (PFKFB3), a potent modulator of glycolysis, is highly expressed in a variety kind of cancers and plays important roles during the whole pathological processes of cancer. It also participates in chemoresistance, which is a major factor in affecting the chemotherapy potency and prognosis of cancer. Compared with their wild-type (WT) cells, cisplatin (DDP) resistant (DDR) cells showed lower capacity of cell viability loss and apoptosis upon DDP treatment, but exhibited higher level of autophagy. Moreover, DDR cells showed higher levels of PFKFB3, and inhibition of PFKFB3 reduced the DDP-induced autophagy. Taking advantage of the tracing property of coumarin conjugated DDP (CP-DDP), we found it could partly co-localize with LC3, and its content lessened faster in DDR cells than that in WT cells.Meanwhile, deprivation of autophagy attenuated the elimination of CP-DDP, and reversed the DDP resistance in DDR cells. Similarly, PFKFB3 deprivation also reduced CP-DDP elimination, and enhanced the cytotoxicity of DDP. Moreover, PFKFB3 inhibitor in combination with DDP led to a marked reduction in tumor growth in the mouse xenograft model. These data suggested that PFKFB3 inhibition reversed DDP resistance and could be used as a therapeutic strategy for colorectal cancer patients.